The rural health initiative: Bridging gaps in healthcare access and grant-funded research in central Idaho - Zigman Suchsland, Monica; van Rensburg, Dillon; McGrath, Kelly; Wilkinson, Cody; Johnson, Kimberly; Steinbruecker, Ashley; Probus, James; Cole, Allison (Journal of clinical and translational science, 2025)
Translational science rarely addresses the needs of rural communities, perpetuating health inequities. Furthermore, policy and resource allocation reflect this dynamic. Through a partnership between a rural community and a community engagement program, the Rural Health Initiative (RHI) was developed with the goal of building capacity for community-driven translational research in rural settings. We describe the process of forming the RHI and selection of a community health priority to motivate the translational research agenda in this particular rural setting. We used a mixed methods approach utilizing literature review, community survey data, and qualitative evaluation of community meeting discussions. Consensus on a final health priority was built through voting and comparison of voting responses across the three RHI counties through Fisher's Exact test. Four priority topics were identified through literature search, community needs assessment, state/national trend data, and community experts. Priority ranking from a community forum and survey selected the final health priority topic. Healthcare access was selected by all three counties in the RHI community as the most critical health priority to address. This program highlights the importance of and methods for community involvement in directing the research conducted in their community. Additionally, through this project, guidance was developed to define the role of community engagement programs supporting work led by communities.